Microsoft ASP.NET AJAX - Bilgin, Asli.; Safari eBooks ([S.l.] : Total Training, 2007)
"Build rich, dynamic, and interactive web applications with the Microsoft AJAX Library. This video series, presented by Asli Bilgin, explores not only the slick user interface controls, but goes deeper into the backbone of a web application. You'll also learn how to work with security, data access, and services orientation so that you can build a robust end-to-end application using Microsoft ASP.NET AJAX and the ASP.NET AJAX Control Toolkit"--Resource description page.
Title from resource description page (viewed Oct. 1, 2009 ).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Microsoft ASP.NET AJAX; Ajax (Web site development technology); Web site development; Electronic books